2021
DOI: 10.7759/cureus.17245
|View full text |Cite
|
Sign up to set email alerts
|

Skin-Lightening Products: Consumer Preferences and Costs

Abstract: Disorders of skin hyperpigmentation have an appreciable impact on quality of life, carrying social and cultural importance that influences widespread consumer demand for cosmetic lightening products. We sought to investigate product factors that may influence consumer preference when choosing an over-thecounter cream for skin-lightening purposes. The keyword "lightening cream" was searched in the "Beauty and Personal Care category" of online retailer Amazon.com. The top fifth percentile of products was determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 18 publications
(20 reference statements)
0
11
0
Order By: Relevance
“…People appear considerably older than they actually are due to these skin changes 6 . The prevalence of skin hyperpigmentation problems affects people’s quality of life and is associated with social and cultural significance, which drives up demand for cosmetic lightening treatments 7 .…”
Section: Introductionmentioning
confidence: 99%
“…People appear considerably older than they actually are due to these skin changes 6 . The prevalence of skin hyperpigmentation problems affects people’s quality of life and is associated with social and cultural significance, which drives up demand for cosmetic lightening treatments 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, there is a growing trend among individuals who want to whiten their skin. The global market for skin-whitening products was 8.3 billion USD in 2018, and the skin-whitening industry is projected to be worth over 24 billion USD by 2027 . Despite extensive research, the precise structure of melanin remains unclear; , however, it has been suggested that interactions such as π – π, π–cation, and hydrogen bonding contribute to the maintenance of the melanin structure. Due to this structural ambiguity, the removal of existing melanin is not straightforward.…”
Section: Introductionmentioning
confidence: 99%
“…Consumers are increasingly looking for depigmenting cosmetic solutions as skin hyperpigmentation disorders have a significant impact on quality of life [ 1 , 2 ]. Furthermore, the increase in life expectancy, along with a growing demand for solutions to combat the effects of aging on the skin, has given rise to a prevalent concern related to aging skin.…”
Section: Introductionmentioning
confidence: 99%